Evaluation of sensitivity and specificity of enzyme-linked immunosorbent assay (ELISA) for detecting antidesmoglein 1 and 3 in Thai patients with pemphigus vulgaris and foliaceus - Suthinee Kulkollakarn (2018)
Objective: Pemphigus is an acquired autoimmune blistering skin diseases, of which pemphigus vulgaris (PV) and pemphigus foliaceus (PF) are two major subtypes. A novel commercial enzyme-linked immunosorbent assay (ELISA) against Dsg1 and Dsg3 has been well established for diagnosis and prediction of disease activity in PF and PV. At present, the benefit of anti-Dsg 1 and anti-Dsg 3 IgG by ELISA in the diagnosis of pemphigus in Thai patients has never been reported. The objective of the present study is to evaluate the sensitivity and specificity of ELISA for detecting antidesmoglein 1 and 3 in Thai patients with pemphigus. Material and Method: Retrospective review of anti-Dsg1 and anti-Dsg3 antibody ELISA test results from 48 serum samples collected from 27 patients with PV, seven patients with PF, and 14 controls. Results: The sensitivity of Dsg1 and Dsg3 ELISA for all patients with PV was 64% and 77.8% respectively. When subgrouped into only PV patients with new diagnosis, the sensitivity of Dsg 1 and Dsg 3 ELISA increased to 85.7% and 100%. In all PF patients, the sensitivity of anti-Dsg 1 ELISA was 71.4% and 100% for newly diagnosed PF cases. Anti-Dsg 3 was not detected in the PF group. The specificity of ELISA for anti-Dsg 1 and anti-Dsg 3 in both types of pemphigus was 85.7% and 92.3% respectively. Conclusion: Dsg 1 and Dsg 3 ELISA is a simple, highly sensitive and specific test in Thai pemphigus patients with 100% sensitivity in the diagnosis of both new pemphigus vulgaris and foliaceus patients.